2008
DOI: 10.1093/eurheartj/ehn166
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol lowering is more important than pleiotropic effects of statins for endothelial function in patients with dysglycaemia and coronary artery disease

Abstract: Lipid lowering is more important than pleiotropic effects of statins for improvement in endothelial function and inflammatory markers in patients with dysglycaemia and CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 43 publications
6
51
0
2
Order By: Relevance
“…1,2 We agree that our patient population had lower cardiovascular risks and higher on-treatment low-density lipoprotein cholesterol (LDL-C) levels. Thus, it is possible that LDL-C lowering alone may not be the overwhelming determinant of endothelial function as observed in our study.…”
mentioning
confidence: 60%
“…1,2 We agree that our patient population had lower cardiovascular risks and higher on-treatment low-density lipoprotein cholesterol (LDL-C) levels. Thus, it is possible that LDL-C lowering alone may not be the overwhelming determinant of endothelial function as observed in our study.…”
mentioning
confidence: 60%
“…24 In another study, 39 patients with either diabetes or impaired fasting glucose, stable CAD, and without lipid-lowering therapy in the previous 3 months were examined with regard to the effects of simvastatin at 80 mg/day and combination therapy with ezetimibe 10 mg + simvastatin 10 mg/day on brachial artery FMD. 25 These studies, however, may not be applicable to CAD patients because it was performed exclusively in subjects with rheumatoid arthritis, a condition that is in itself highly associated with inflammation and endothelial dysfunction. 26 In the latter study, as described, the sole effect of simvastatin at 10 mg on endothelial function was not evaluated, and the study de- with Rho-associated kinase activity, 36 which has been shown to be a contributing factor in endothelial dysfunction and vascular disease.…”
Section: -31mentioning
confidence: 99%
“…There was no difference between selective ET A and dual receptor blockade in this patient group, however. Furthermore, dual ET A /ET B receptor blockade with BQ123 and BQ788 elicited forearm vasodilatation in patients with atherosclerosis and type 2 diabetes mellitus (Settergren et al, 2007a, manuscript in preparation; [98]). It is also of interest to note that ET A receptor blockade increases nutritive skin capillary blood flow in patients with type 2 diabetes and microangiopathy, whereas no effect was observed in agematched controls (Settergren et al, 2007b, manuscript in preparation; [99]).…”
Section: % + Increased Temperaturementioning
confidence: 99%